Epidemiological and Clinical Characteristics of Hospitalized Pediatric Patients with SARS-CoV-2 Infection in Mexico City, Mexico - Gustavo Esteban Lugo-Zamudio; Antonio Aguilar-Rojas; Martín Uriel Vázquez-Medina; Antonio Gutiérrez-Ramírez; Ma. Cristina Upton-Alvarado; Patricia Espinoza-Rivas; Gustavo Lagunas-Torres; María Isabel Rojo-Gutiérrez; Gabriela Ibáñez-Cervantes; Cruz Vargas-De-León (Canadian Journal of Infectious Diseases and Medical Microbiology, 2022)
Background. Evidence from across the world suggests that the pediatric population shows different clinical manifestations and has a lower risk of severe presentation of SARS-CoV-2 infection compared to adults. However, Mexico has one of the highest mortality rates in the pediatric population due to SARS-CoV-2 infection. Therefore, our objective was to explore the epidemiological and clinical characteristics associated with a positive confirmatory test in the Mexican pediatric population admitted to a tertiary care hospital in Mexico City. Methods. Clinical, imaging and laboratory data were retrospectively collected from 121 children hospitalized during the period from March 4th, 2020, to August 8th, 2021. The patients were identified as suspicious cases according to the guidelines of the General Directorate of Epidemiology of Mexico. Real-time polymerase chain reaction (RT-PCR) tests were used to confirm SARS-CoV-2 infection. Categorical variables were compared using the Chi-square test, and propensity score matching was performed to determine univariate and multivariate odds ratios of the population regarding a positive vs. negative SARS-CoV-2 result. Results. Of the 121 children, 36 had laboratory-confirmed SARS-CoV-2 infection. The main risk for SARS-CoV-2-associated pediatric hospitalization was contact with a family member with SARS-CoV-2. It was also found that fever and fatigue were statistically significantly associated with a positive SARS-CoV-2 test in multivariate models. Clinical and laboratory data in this Mexican hospitalized pediatric cohort differ from other reports worldwide; the mortality rate (1.6%) of the population studied was higher than that seen in reports from other countries. Conclusion. Our study found that fever and fatigue at hospital presentation as well as an antecedent exposure to a family member with SARS-CoV-2 infection were important risk factors for SARS-CoV-2 positivity in children at hospital admission.